Axis specific player load to quantify lower limb biomechanical loading in adolescent badminton players - Wylde, M. J.; Kumar, B.; Young, L. C.; Callaway, A. J. (International Journal of Racket Sports Science, 2019)
While the use of accelerometer derived Player Load has become increasingly prominent, the limitation of this approach is that training load is reduced to a single number with no differentiation between the mechanisms of loading, resulting in a loss of context. As recovery from different loadings occur at different rates, the inability to differentiate between the loading mechanisms could lead to under or over training in one or more of these mechanisms. This study sought to compare axis specific accelerometer derived Player Load with differential RPE scores to establish a means of quantifying the lower limb biomechanical load of adolescent badminton training, to try and understand some of the context into the Player Load number. It was postulated that the Player Load from the vertical axis would provide a more precise measure of lower limb loading as other loading parameters, such as upper body rotation observed during a smash, would be removed from the calculation. Nineteen adolescent badminton players (Age:14.0 ± 0.8 y) based at a dedicated high performance youth training environment wore a GPS-embedded accelerometer between the scapulae in a purpose built vest during court-based training. After each training session the participants provided two RPE scores, one localised for the legs and one for breathlessness. Overall low correlations were observed between the Player Load and RPE values. The Player Load for the vertical axis showed a stronger correlation with the RPE for breathlessness than the RPE for thelower limb stress.The results from this study suggest that axis specific Player Load from the vertical axis does not provide greater insight into lower-limb biomechanical load compared to overall Player Load in adolescent badminton players.